Mubtada Khobar In Surah Saba' and Learning Media For Beginners - Khasanah, Nadho Fatun; Rosid, Abdur; Ulya , Makhilatus Suhuril; Farkhah, Taliya; Sunarko, Asep (DAS Institute, 2023)
This research aims to find out the structure of mubtada and khobar found in Surat Saba', as well as determine the appropriate media in mubtada and khobar learning for beginners, in library research. This research has a qualitative pattern and the research object is in the form of learning media that is explained with descriptive words so that it can be easily understood. Based on the data analysis that has been done on surah Saba' there are 37 mubtada' and khobar, the media that is suitable for learning mubtada and khobar is visual media.